A Participatory Approach to Develop Ethical Guidelines for Generative Artificial Intelligence - Shaukat, Fatima; Kamal, Zainab; Khan, Rehan Ahmed; Sajjad, Madiha; Tassaduq, Irum; Ambreen , Salma (Pakistan Armed Forces Medical Journal, 2025)
Objective: To explore the perceptions of supervisors and postgraduate students on the ethical use of Artificial Intelligence (AI) in thesis writing.Study Design: Qualitative Exploratory Study.Place and Duration of Study: Riphah International University Rawalpindi, Pakistan from Jan to Jun 2024.Methodology: Focus group discussions were employed to gather data from 20 participants, consisting of university supervisors and postgraduate students. Thematic analysis was performed using ATLAS.ti 9 to identify recurring themes related to the ethical use of AI in thesis writing.Results: Five key themes emerged from the analysis: transparency, academic integrity, personal development, data privacy, and supervision. Both students and supervisors expressed concerns about the ethical use of AI, particularly around issues like plagiarism, over-reliance, and data security. Supervisors also emphasized the need for institutional policies to regulate AI usage, while students perceived AI as a tool for enhancing their academic skills.Conclusion: There is a critical need for comprehensive ethical guidelines to govern the use of AI in academic research, particularly in thesis writing. Engagement of key stakeholder including academic supervisors, students, and institutional authorities in the formulation of these guidelines provided a balanced approach in identifying the benefits of AI while addressing concerns related to academic integrity, transparency, and data privacy.